FUNDAMENTAL PEDAGOGI DALAM PERSPEKTIF AGAMA BUDDHA - Edi Ramawijaya Putra (Jurnal Ilmiah Kampus: Sati Sampajanna, 2019)
This article presents several fundamental perspectives which are derivatively generated frombuddhism point of view. The peripheral basis of buddhist teaching, ethics, and spiritual goals have longbeen acquainted with the practices of modern education worldwide. The absorbances may representedby the accommodation of practical ethics, values and insights for both management, practical,pedagogocal and educational policies. However, there are many misundersanding and misconceptiontoward the application of buddhist pedagogy in school-system environment, educators‟ behaviors aswell as the outcomes in the curriculum. Therefore, revitalization and re-orientation should be madetowards the on-going practices of today‟s buddhist education and whole stakeholders within. As aframework, buddhist fundamental pedagogy must be able to transform human being and helping themto develop potentials. For long term purpose, buddhist education must also educate spiritualengagement with life, contextual surrounding and social phenomenon for better humanity andspirituality. Finally, as a result, buddhist education should have assigned its goal for positiveoutcomes and regards to the current situation of today‟s livelihood.